Cancer risk associated with DPP4 inhibitors in type 2 diabetes: A pharmacovigilance analysis of the FDA Adverse Event Reporting System (FAERS) - Wan Xiong; Yilin Li; Juanjuan Huang; Gefei He; Ji Sun (PLoS ONE, 2026)
Background The use of dipeptidyl peptidase 4 (DPP4) inhibitors in treating type 2 diabetes mellitus (T2DM) is increasingly widespread. However, their association with malignancy risk has not been comprehensively evaluated in real-world clinical settings. This study, utilizing the Food and Drug Adverse Event Reporting System (FAERS) database, investigated the potential link between DPP4 inhibitors and malignancies. Methods Data from the FAERS database (January 2019 to December 2024) were analyzed. Descriptive statistics assessed patient demographics for each drug-event combination, while disproportionality analysis based on Reporting Odds Ratio (ROR) and Information Component (IC) metrics valuated cancer-related adverse event (AE) risks. Binary logistic regression was used to minimize potential bias. Results A comprehensive analysis identified 3,764 AE reports linked to malignancies in T2DM individuals treated with DPP4 inhibitors. Signal detection analysis revealed that sitagliptin exhibited the strongest and most extensive positive signals across both the Preferred Terms and Standardized Medical Dictionary for Regulatory Activities Queries. Specifically, significant signals were observed for malignancies (ROR 025 : 13.80, IC 025 : 3.48), tumor lysis syndrome (ROR 025 : 5.79, IC 025 : 2.32), and site-specific neoplasms (e.g., uterine, fallopian tube, and prostate). Age distribution analysis indicated that the median age of individuals reporting malignancy-related AEs exceeded 70 years in most drug groups. Furthermore, in studies with larger sample sizes, the median time to AE onset for for DPP4 inhibitors ranged from 13 to 15 months. Conclusions This study demonstrates significant associations between all five DPP4 inhibitors and malignancy-related AEs, with sitagliptin showing the highest risk profile. These findings highlight the need for further validation through large-scale prospective studies to verify the observed pharmacovigilance signals and to elucidate their potential clinical significance and underlying biological mechanisms.